2022
DOI: 10.3390/genes13030448
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Adjusted for Occupational and Environmental Factors for Bladder Cancer Susceptibility

Abstract: This study examined the effects of single-nucleotide polymorphisms (SNPs) on the development of bladder cancer, adding longest-held occupational and industrial history as regulators. The genome purified from blood was genotyped, followed by SNP imputation. In the genome-wide association study (GWAS), several patterns of industrial/occupational classifications were added to logistic regression models. The association test between bladder cancer development and the calculated genetic score for each gene region w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Zaitsu et al [9] created a new taxonomy (tentatively named the Zaitsu classification) that combines the classifications of industrial and occupational history to create 12 different categories [15,16].…”
Section: Zaitsu Classification Of Industry/occupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Zaitsu et al [9] created a new taxonomy (tentatively named the Zaitsu classification) that combines the classifications of industrial and occupational history to create 12 different categories [15,16].…”
Section: Zaitsu Classification Of Industry/occupationmentioning
confidence: 99%
“…The genotyping of samples, quality control of samples, quality control of genotypes, and SNP imputation were previously described [16].…”
Section: Genotypingmentioning
confidence: 99%
“…Interestingly, first-degree relatives of patients with BC had a two-fold increased risk of developing this cancer [ 11 , 12 ]. However, a recent genome-wide association study (GWAS) adjusted for occupational and environmental factors for bladder cancer susceptibility confirmed that the influence of genetic factors favouring the development of BC was modified by environmental factors, especially stress stimulation and work environment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%